12x-3(2x-3)=9+6x

Simple and best practice solution for 12x-3(2x-3)=9+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3(2x-3)=9+6x equation:


Simplifying
12x + -3(2x + -3) = 9 + 6x

Reorder the terms:
12x + -3(-3 + 2x) = 9 + 6x
12x + (-3 * -3 + 2x * -3) = 9 + 6x
12x + (9 + -6x) = 9 + 6x

Reorder the terms:
9 + 12x + -6x = 9 + 6x

Combine like terms: 12x + -6x = 6x
9 + 6x = 9 + 6x

Add '-9' to each side of the equation.
9 + -9 + 6x = 9 + -9 + 6x

Combine like terms: 9 + -9 = 0
0 + 6x = 9 + -9 + 6x
6x = 9 + -9 + 6x

Combine like terms: 9 + -9 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 22x-4(3x-6)=24+10x | | (y-15)=-12/17 | | 29/3 | | 11x-2(3x-5)=14+5x | | 89/9 | | 4x-5(x+1)=7 | | 16x-2(3x-3)=8+10x | | .5y=3x-1 | | -10x-3=-5(2x+8)+37 | | 3w+4w-3=32 | | -6x-2=-3(2x+8)+22 | | -20x-11=-5(4x+5) | | y=(x^2-25)(x+2i)(x-2i) | | -26x-8=-7(4x+3) | | -5x-7=-4(2x+4) | | v=x^2*h | | 7(4x-6)+5x=4x-42+29x | | 4-y=1-y | | 3+7*7+3= | | 7(5x-4)+6x=3x-21+34x | | 4(4x-5)+5x=4x-15+13x | | 6(7x-2)+7x=3x-14+46x | | 3x+11=3x+13 | | -7y=-2x+1 | | 9x+13=6x+11 | | 11x+8=8x+7 | | x/7-y/2=1 | | 4w/2w^3 | | 3xy-21x+2z-14=0 | | 4(2x+5)-3(5x-5)=1 | | 5x+4y=110000 | | Log(9)7-log(9)4= |

Equations solver categories